Transarterial embolization for renal angiomyolipomas: A single centre experience in 79 patients. (April 2017) - Wang, Chengen; Yang, Min; Tong, Xiaoqiang; Wang, Jian; Guan, Haitao; Niu, Guochen; Yan, Ziguang; Zhang, Bihui; Zou, Yinghua
Objective: To evaluate the long-term efficacy and safety of selective arterial embolization (SAE) in the treatment of renal angiomyolipomas (AMLs). Methods: This was a retrospective review of medical records and imaging findings from patients with renal AMLs who attended our clinic and received SAE between January 2007 and January 2014. Only patents with complete medical records, preoperative computed tomography scans using typical imaging and follow-up data were included. Results: A total of 79 patients were enrolled in the study. Technical and clinical success rates were 100% and 91% ( n = 72), respectively. Only two patients experienced major complications. Post-embolization syndrome (i.e. fever, abdominal pain, nausea or vomiting) was reported in 68 (86%) patients, but all symptoms were mild and resolved with conservative measures. Mean radiological and clinical follow-up periods were 16.8 and 35.9 months, respectively. In 75 (95%) patients, tumours decreased in size; mean ± SD tumour size significantly decreased from 8.4 ± 3.5 cm pre-embolization to 6.7 ± 3.0 cm post-embolization . Conclusions: This study provides long-term evidence that SAE is a safe and effective method in the treatment of patients with renal AMLs.